To what extent do principals of further education colleges display similar leadership traits? - Lambert, Dr. Steve (IJRDO - Journal of Applied Management Science, 2017)
Principals of further education colleges continue to operate in a policy context driven by reductions in funding, increasing diversity among the student population and escalating centralised control. This has meant that principals are required to rely more on their skills as decision makers and problem solvers than they have every needed in the past. At the same time, external inspection has continued to highlight the importance of leadership in enabling students to achieve the best possible outcomes, yet as Fink (2010) argues the role of the principal is becoming increasingly unattractive. In order to combat a shortage of individuals pursuing principalship positions, organisations are developing their own leadership development programmes; however, little is known about the behaviours that these programmes should be developing. This paper reports the findings of a series of leadership and psychological assessments conducted with principals within the UK. It suggests that despite the organisational and political challenges facing institutions principals demonstrate a largely homogenous set of behaviours which could be used to frame future leadership development programmes.